Desenvolvimento de metodologias sintéticas visando a preparação de quinonas contendo calcogênio: potentes compostos antitumorais com dois centros redox - Wagner de Oliveira Valença (2017)
In the present work, the chalcogenylation of p-naphthoquinones (21 examples) was carried out using lapachol and ,3-dibromo-1,4-naphthoquinone as starting materialswith excess of different electrophiles containing selenium and sulfur nucleophiles. For the calcogenylation of lapachol, DMSO was used as a stoichiometric oxidant, molecular iodine as catalyst and different electrophiles containing selenium or sulfur. Under microwaveirradiation the compounds were obtained in moderate to excellent yields (50-94%). The calcogenylation of 2,3-dibromo-1,4-naphthoquinone (10 examples) was performed under reflux in ethanol with excess of different sulfur-containing nucleophiles, in order to obtain 1,4-naphthoquinone derivatives in low to excellent yields (30-86%). Next, novel 1,2,3-triazole naphthoquinoidal derivatives containing the sulfur atom (19 examples) were prepared using the corresponding naphthoquinones with excess tosylazide as starting material and CuTC as the as the catalyst. In this way, novel N-sulfonyl-1,2,3-triazoles wereobtained in yields ranging from 30 to 98%. The new triazolic compounds derived from 1,4-naphthoquinone were subjected to catalysis using rhodium complexes, and the sulphonamido-naphthoquinoidal derivative was obtained with excellent yield (94%) when 10 mol% of Rh2(Esp)2 catalyst was used in dichloromethane in a 0.05M, at 85ºC for 12h.The compounds were characterized by 1H and 13C nuclear magnetic resonance spectroscopy, infrared and high resolution mass spectrometry. Calcogen-bound ß-lapachones and sulfur atom-containing triazole p-naphthoquinones were tested in vitro against normal and tumor lines and showed promising results.